2012
DOI: 10.1590/s1808-18512012000100008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade de vida em pacientes submetidos à cirurgia de estenose de canal lombar com mais de 60 anos

Abstract: OBJETIVO: Avaliar as mudanças na qualidade de vida antes e após a cirurgia de artrodese lombar através dos questionários Owestry Disablity Index (ODI), Roland-Morris (RM) e Escala Analógica Visual (VAS). MÉTODOS: Foram avaliadas as mudanças nos questionários (ODI, RM e VAS) entre o pré-operatório, 1 semana, 1 mês, 2 meses, 6 meses, 1 ano e 2 anos após o procedimento cirúrgico. RESULTADOS: Foram estudados 38 pacientes com idade acima de 60 anos com acompanhamento de pelo menos dois anos. Houve uma melhora no OD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…In the non-operated group, we hypothesized that the results might be due to the pain when analyzing the effort made during spirometry. 6,12,[17][18][19] With respect to the other spirometric variables evaluated in our study, FEV 1 , FEF 25-75% and PEF showed no statistically significant difference between the two groups, and those results were expected due to the greater relationship between these variables and obstructive patterns, and one of the exclusion criteria was precisely that the particpant presented with pulmonary disease. 19,20 In analyzing the strength of respiratory muscles, the operated group obtained higher than average values of MIP and MEP when compared to the non-operated group.…”
Section: Discussionmentioning
confidence: 44%
“…In the non-operated group, we hypothesized that the results might be due to the pain when analyzing the effort made during spirometry. 6,12,[17][18][19] With respect to the other spirometric variables evaluated in our study, FEV 1 , FEF 25-75% and PEF showed no statistically significant difference between the two groups, and those results were expected due to the greater relationship between these variables and obstructive patterns, and one of the exclusion criteria was precisely that the particpant presented with pulmonary disease. 19,20 In analyzing the strength of respiratory muscles, the operated group obtained higher than average values of MIP and MEP when compared to the non-operated group.…”
Section: Discussionmentioning
confidence: 44%
“…Ainda, observamos na literatura indivíduos com médias acima de 60% no grau de limitação funcional, medida também pelo ODI, e que também possuíam doenças como estenose espinhal, espondilolistese e hérnia de disco (LEITE et al;KRISHNA, et al, 2014;YOSHINO;RODRIGUES, 2012). E para pacientes com problemas na região cervical encontramos médias menores do que 19% (PARK, et al, 2013, CARR et al, 2011.…”
Section: é T O D O | 40unclassified
“…E neste período foram realizados tratamentos conservadores, como: fisioterapia e utilização de medicamentos, porém os pacientes não obtiveram resultados positivos e então seus médicos optaram pelo tratamento cirúrgico (CARR et al, 2011;LEITE et al;KRISHNA, et al, 2014;PARK, et al, 2013;YOSHINO;RODRIGUES, 2012).…”
Section: é T O D O | 40unclassified